IMMUNE STATUS IN PATIENTS WITH BENIGN PROSTATIC HYPERPLASIA - Gulyamov M.Kh., (Central Asian Journal of Medicine, 2025)
The purpose of the study was to conduct a comparative analysis of the immune status of patients with benign prostatic hyperplasia (BPH) after various surgical interventions: endoscopic ablation of the prostate (EAP), transurethral resection of the prostate (TUR) and traditional adenomectomy. Eighty patients were included in the study: 20 underwent EAP, 20 underwent TUR, and 40 underwent traditional adenomectomy. The indices of cellular and humoral immunity in the preoperative and postoperative periods were studied. Differences in the immune response of the organism depending on the applied method of treatment were revealed.